(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the nutritional status and associated factors among patients with gastric and colorectal cancer undergoing chemotherapy at Bai Chay General Hospital in 2025. Methods: A cross-sectional descriptive study was conducted on 109 patients. Results: Males accounted for 69.7%; the mean age was 60.9±11.7 years, with patients aged >60 years comprising 60.7%. Rectal cancer accounted for 45.0%, colon cancer 36.7%, and gastric cancer 18.3%; most patients were at stage III–IV (89%). The mean number of chemotherapy cycles was 4.1±2.1. Based on BMI, 67.0% had normal nutritional status, while 29.4% were malnourished. According to PG-SGA classification, 62.4% were categorized as A, 26.6% as B, and 11.0% as C. Weight loss was common: 62.4% lost weight within 1 month (2.7±2.1 kg) and 76.1% within 6 months (4.0±3.0 kg). Within 1 month, 57.8% reported reduced food intake, mainly consuming less than usual. Patients with fewer than 5 chemotherapy cycles had a 5.1-fold higher risk of severe malnutrition (95% CI: 1.2–20.8; p=0.021). Hypoalbuminemia was significantly associated with severe malnutrition (p<0.001), whereas cancer stage and diagnosis showed no clear association. Conclusion: Malnutrition and weight loss are common among patients with gastrointestinal cancers undergoing chemotherapy. PG-SGA is a useful tool for early detection, and routine nutritional screening and intervention should be strengthened in clinical practice.